Chromosome-plasmid interaction in Escherichia coli K-12 carrying a thermosensitive plasmid, Rts1, in autonomous and in integrated states. - Yoshimoto, H (1975)
An Hfr strain of Escherichia coli K-12 was obtained by integrative suppression with a thermosensitive plasmid, Rts1. The R plasmid was integrated into the chromosome between rif and thr, and transfer of the chromosome occurred counterclockwise. The thermosensitivity of host cell growth due to the dnaA mutation was markedly but not completely reduced in this integratively suppressed Hfr strain. When the dnaA mutation was removed by transducing the dnaA+ genome to this Hfr, the thermosensitivity of cell growth due to existence of Rts1 was suppressed in contrast to strains carrying it autonomously. Thermosensitivity of cell growth appeared again when the plasmid was detached from the chromosome to exist autonomously. Contrary to the effect on cell growth, the transfer of the chromosome and the plasmid itself and the ability to "restrict" T-even phages were still thermosensitive in all of these strains carrying Rts1, irrespective of its state of existence. The detached plasmid as well as the original Rts1 were segregated upon growth at 42 C. These data are discussed in relation to chromosome-plasmid interaction. One of the most important conculusions is that some plasmid genes, related to their replication, are phenotypically suppressed by the chromosome when it is integrated.